Simulation of Storage Performance on Hydropneumatic Driveline in Dual Hybrid Hydraulic Passenger Car - F., Wasbari; R. A., Bakar; Gan, Leong Ming; Ahmad Anas, Yusof; Zarina, Amat Jafar (EDP Sciences, 2016)
The charging process is one of the critical processes in the hydro-pneumatic driveline storage system. It converts the kinetic energy of the vehicle braking and coasting to the compression energy. This energy is stored in the storage device called the accumulator. The system is planned to be used on the dual hydro-pneumatic hybrid driveline and applied to a hydraulic hybrid passenger car. The aim of this paper is to find the effect of charging parameters on the storage performance through simulation. Through the storage behaviour, the desirable and optimal sizing of the accumulator can be selected. The paper emphasized on the effect of pressure elevation, pre-charge pressure, effective volume, thermal reaction and required time of the accumulator’s charging process. The circuit of charging process has been designed and simulated by using the hydraulic tool in the Automation Studio software. The simulation results were corroborated through the component specification for data rationality. Through the simulation, it was found that pre-charge pressure had a significant effect on the charging process. It determined the efficiency of the effective volume. The higher the pressure elevation, the higher the effective volume. Nevertheless, the more energy required to compress the nitrogen gas in the bladder. Besides, in term of volume displacement, higher volume displacement reduced charging time and lower the fluid temperature. The simulation had been positively highlighted the critical point in charging process which later on, benefited the sizing process in the component selection specification.